Manipulation in Negotiations: The Hidden Costs of the “Easy” Victory - Daniel Malutan (Journal of Research and Innovation for Sustainable Society)
Negotiation is a dynamic process where influence plays a key role. This article examines the contrasting approaches of manipulation and ethical persuasion, focusing on their characteristics, implications, and long-term impact. Manipulation, which exploits emotional and cognitive vulnerabilities through deceptive tactics, often delivers short-term gains but undermines trust, collaboration, and reputation. In contrast, ethical persuasion emphasizes transparency, mutual respect, and sustainable relationships. The article explores the historical evolution of manipulation, from ancient rhetoric to its modern manifestations in digital contexts, highlighting the risks and relevance of these practices. It also examines the hidden costs of manipulation, including trust erosion, relational damage, and legal and reputational risks. As a solution, the Harvard Method of principled negotiation is presented as an effective framework for achieving equitable and durable outcomes. This approach emphasizes focusing on interests rather than positions, using objective criteria, and separating people from the problem. Active listening and empathy further enhance this process, fostering mutual understanding and preventing conflict escalation. In an interconnected world, ethical negotiation strategies are vital for long-term success. By contrasting manipulation and persuasion, the article provides insights into cultivating trust, collaboration, and integrity in negotiations.